2012
DOI: 10.1117/1.oe.51.11.111702
|View full text |Cite
|
Sign up to set email alerts
|

Snapshot advantage: a review of the light collection improvement for parallel high-dimensional measurement systems

Abstract: The snapshot advantage is a large increase in light collection efficiency available to high-dimensional measurement systems that avoid filtering and scanning. After discussing this advantage in the context of imaging spectrometry, where the greatest effort towards developing snapshot systems has been made, we describe the types of measurements where it is applicable. We then generalize it to the larger context of high-dimensional measurements, where the advantage increases geometrically with measurement dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 52 publications
1
81
0
Order By: Relevance
“…More precise measurements would require a more thorough spectral and intensity calibration. It should however be noted that thanks to the colocation property not only such a calibration is relatively straightforward to apply compared to existing techniques (Hagen et al, 2012), but also it is not required to obtain reasonably accurate results, as shown by our preliminary results.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…More precise measurements would require a more thorough spectral and intensity calibration. It should however be noted that thanks to the colocation property not only such a calibration is relatively straightforward to apply compared to existing techniques (Hagen et al, 2012), but also it is not required to obtain reasonably accurate results, as shown by our preliminary results.…”
Section: Resultsmentioning
confidence: 61%
“…Many alternative methods have been proposed to improve this process by capturing the full hyperspectral cube in a single snapshot (see (Hagen et al, 2012), and a thorough recent review in (Hagen and Kudenov, 2013)). Some rely on a complex optical design that implies the use of lenslet arrays, slicing faceted mirrors, mosaic filters on the imaging device, series of spectral filters, series of image detectors... Much simpler "computational sensing" designs recently appeared, in which a single image detector is implied.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst other techniques, this can be performed by an image slicer, i.e., a mirror stack followed by a recombining optic, or by use of a fiber bundle. Fiber bundle-coupled IFS is also called FAST (fiber array spectral translation, Stewart et al, 2012) or FRIS (fiber-reformatting imaging spectroscopy, Hagen et al, 2012). Figure 1 describes the concept.…”
Section: Fiber Bundle-coupled Astronomy Spectrographmentioning
confidence: 99%
“…Even for an image being composed of some 100 pixels, the measurement time can exceed 1 h. For examination at a patient or for fast-changing samples, this time span is far too long to be practical. To accelerate the measuring procedure, various techniques for a parallel data collection are described (Li et al, 2013;Hagen et al, 2012). Of particular interest are full-throughput snapshot techniques, also called multichannel or integral field spectroscopy (IFS).…”
Section: Introductionmentioning
confidence: 99%
“…A number of technologies have been developed including, whiskbroom and pushbroom where a 1 or 2D detector array is used to scan a column or slice of the datacube [3], a filtered camera to record slices scanned along the spectral dimension [4] and Fourier-transform imaging spectrometry [5][6][7]. Snapshot imaging spectrometers, on the other hand, can record the entire datacube without the need for scanning and have the advantage of improved light-collection efficiency [8].…”
Section: Introductionmentioning
confidence: 99%